(untitled) (Research, Society and Development, 2023)
Introduction: Localized juvenile spongiotic gingival hyperplasia (LJSGH) is an uncommon benign pathology, first mentioned in 2007 by Darling et al. It is characterized by presenting as a painless solitary gingival mass, bright red in color, velvety in appearance and prone to bleeding on tooth brushing, its cause is unknown. It usually affects a discrete area of the attached gingiva. Methodology: A review of the literature was carried out in different digital databases such as PubMed, Science Direct, Medigraphic and ELSEVIER, compiling relevant information that justifies the findings of the present clinical case of a female patient. Results: Clinical features such as its reddish color, texture and location were key indicators for LJSGH, in addition to the absence of response to oral hygiene measures. Conclusion: Juvenile spongiotic gingival hyperplasia is defined as a rare clinical pathological entity that dentists might encounter in their practice, it is important to know this pathology in order to diagnose it properly.